The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/s1678-9946201961020
|View full text |Cite
|
Sign up to set email alerts
|

Virulence factors and integrons are associated with MDR and XDR phenotypes in nosocomial strains of Pseudomonas aeruginosa in a Venezuelan university hospital

Abstract: Multidrug resistance (MDR), virulence and transferable elements potentiate Pseudomonas aeruginosa 's role as an opportunistic pathogen creating a high risk for public health. In this study, we evaluated the possible association of multidrug resistance, virulence factors and integrons with intrahospital P. aeruginosa strains isolated from patients at Cumana hospital, Venezuela. Relevant clinical-epidemiological data were collected to study 176 strains (2009-2016) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 34 publications
7
15
1
Order By: Relevance
“…Additionally, many authors described a significant positive correlation between MBL and AmpC β-lactamase production and biofilm formation 35. In contrast to our results, other studies found no significant difference in the association of biofilm formation and the presence of multidrug resistance 22,36. Also, no statistical significance was found between MBL and biofilm formation 31…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Additionally, many authors described a significant positive correlation between MBL and AmpC β-lactamase production and biofilm formation 35. In contrast to our results, other studies found no significant difference in the association of biofilm formation and the presence of multidrug resistance 22,36. Also, no statistical significance was found between MBL and biofilm formation 31…”
Section: Discussioncontrasting
confidence: 99%
“…The same finding was previously reported 23,29. This high rate of imipenem resistance may be due to uncontrolled carbapenem use in hospital infections 22. Carbapenem resistance among P. aeruginosa isolates is attributed mainly to carbapenemase production 5.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…30 We found a high frequency of exoU in our isolates indicating that more than half of the isolates display the cytotoxic phenotype, 31 which is associated with more pulmonary damage than invasive phenotypes. 32 This finding is consistent with Rodulfo et al, 33 who found a high frequency of exoU in MDR P. aeruginosa isolates. On the other hand, exoS was detected in a relatively similar frequency as exoU; with 17 isolates (43%) harboring exoS gene alone and 3 isolates possessing both genes (7.6%).…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the presence of Car-R/Ceph-S isolates (reported to be~13% of the overall pool of isolates), their report highlighted the continuous increase in resistance rates to β-lactam antibiotics and class I integrons between 2009 and 2016 (37.1% vs. 50.0% for piperacillin-tazobactam, 32.3% vs. 50% for ceftazidime, 33.9% vs. 50% for cefepime, 38.7% vs. 65.6% for imipenem, and 37.1% vs. 59.4% for meropenem). They have also found a positive association between the MDR/XDR phenotype and the presence of hemolysin, the exoU gene, and integrase I [243]. In the study of Khan et al, the resistance characteristics of keratitis-causing P. aeruginosa isolates, originating from Australia and India, were compared [73].…”
Section: Carbapenem-resistant But Cephalosporin-susceptible P Aerugimentioning
confidence: 99%